Transformations of the form and façade of the Lehndorff palace in Sztynort Duży in the light of architectural research - Bakalarczyk, Szymon (Przekształcenia bryły i elewacji pałacu Lehndorffów w Sztynorcie Dużym w świetle badań architektonicznych, 2023)
Rural residential architecture of former East Prussia is a poorly recognized resource, and therefore often marginalized, or superficially assessed on the basis of contemporary visible stylistic features and assumptions related to the chronology of their transformations. This problem also applies to the baroque Lehndorff palace in Sztynort Duży, which is the second largest, preserved to this day modern family residence in the Warmian-Masurian Voivodeship. The article attempts to recognize the transformations of the form and façade of this building in the light of architectural research. It presents the current state of knowledge and questions raised by the previous authors. Then it discusses the new findings made during the architectural research of the wall structures of the palace façade, taking into account the secondarily obscured perimeter walls. As a result of the observation of changes in the bond, brick material, mortars, plasters and architectural details, juxtaposed with the analysis of published sources, bibliography and some extensive archival materials, eight main construction phases were distinguished. Research resulted in significant changes in the chronology and verification of hypotheses related to undated iconographic sources. It confirmed former hypothesis, that the baroque palace from 1689–1695 had no corner or side avant-corps until the neoclassical expansion. The original composition and color scheme of the façade from that period were determined, as well as new casesuras of both later extensions of the building. The classicist wings were built in the years 1780–1785, and raised in the beginning of 19th century. The neo-Gothic expansion, including raising them again and adding three annexes, was carried out in three stages between 1858–1862. Since then, façades have undergone only minor changes in the area of window openings, mainly in the 1st half of the 20th century, the 1980s, and between 2010 and 2015.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 15-25
Keywords: architektura; palace; Baroque; architectural research; Lehndorff; pałace; barok; badania architektoniczne